(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The study aimed to examine the protective role of plant growth regulators and ascorbic acid against NaCl-induced oxidative damage in onion, to enhance its salinity tolerance mechanism. Onion seeds were subjected to salt stress (10 dS/m) and primed with 30 ppm gibberellic acid (GA3), 1-naphthylacetic acid (NAA), salicylic acid (SA), and ascorbic acid (AsA). Additionally, onion plants were sprayed with 100 ppm of these chemicals. The application of 30 ppm GA₃, AsA, and SA significantly enhanced seed germination percentage, vigor, energy of germination, and shoot-root length, while reducing mean germination time. In contrast, NAA negatively affected germination by lowering energy of germination and shoot-root length. The highest germination percentage (87.92%) was recorded with SA, followed by GA₃ at 69.58%, while the lowest (49.17%) was observed in the control and NAA treatments. Foliar application of 100 ppm SA resulted in the highest bulb yield (15.04 t/ha) under saline stress, along with improvements in yield-contributing parameters. This yield was statistically similar to those obtained from GA₃ and AsA treatments. In contrast, NAA treatment showed no significant difference from the control. The study highlights SA as a potential PGR for improving onion productivity, offering a valuable approach for mitigating salt stress in onion cultivation. J Bangladesh Agril Univ 23(3): 296–303, 2025